Implementation of AI in Animated Health Education Film to Overcome Hospital Anxiety - Rudi Setiawan; Nurhasan Nugroho; Gerald Untirtha Pratama (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Children's fear of going to hospitals is a common emotional barrier that can interfere with medical treatment and early health education. This research addresses that issue by developing an animated educational film using artificial intelligence (AI) to help children aged 6–9 overcome their anxiety about medical environments. The purpose of this study is to produce a multimedia-based health education tool that is emotionally engaging, educationally effective, and technically efficient. The film development followed the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. Several AI-based tools were integrated, including ChatGPT for scriptwriting and visual prompting, Kling AI for animation and lip-syncing, ElevenLabs for AI-generated voice-over, and CapCut for final editing. The result is a 7-minute 2D animation titled